2020
DOI: 10.1186/s12904-020-00663-5
|View full text |Cite
|
Sign up to set email alerts
|

South African paramedic perspectives on prehospital palliative care

Abstract: Background Palliative care is typically performed in-hospital. However, Emergency Medical Service (EMS) providers are uniquely positioned to deliver early palliative care as they are often the first point of medical contact. The aim of this study was to gather the perspectives of advanced life support (ALS) providers within the South African private EMS sector regarding pre-hospital palliative care in terms of its importance, feasibility and barriers to its practice. Methods A qualitative study design employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…If only 47 (40%) of paramedics reported prior formal POLST training, this demonstrates a major curriculum gap and an area for targeted future trainings. The findings of this study are overall consistent with previous literature that demonstrates a paucity of formal training and guidelines around caring for patients near the end of life [ 10 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…If only 47 (40%) of paramedics reported prior formal POLST training, this demonstrates a major curriculum gap and an area for targeted future trainings. The findings of this study are overall consistent with previous literature that demonstrates a paucity of formal training and guidelines around caring for patients near the end of life [ 10 , 11 , 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…2730 Paramedics are trained in decision-making processes, communication, handover processes, analgesic care, and acting as mediators between the pre- and in-hospital services. 17 These competencies may also help them to offer palliative care. Previous studies 9,17,18,23,24,31 have shown that conflicts in care goals, legal issues, organizational policy, and clinical practice guidelines may challenge paramedics when treating palliative patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 These competencies may also help them to offer palliative care. Previous studies 9,17,18,23,24,31 have shown that conflicts in care goals, legal issues, organizational policy, and clinical practice guidelines may challenge paramedics when treating palliative patients. Paramedics report minimal training in palliative care 8,14,17,32 although further education may improve their competency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the phenomenon of EMS responses to patients enrolled in hospice programs could support patient-and family-centered end-of-life care, improve the working interface between EMS systems and hospice programs, and optimize utilization of EMS resources. Numerous studies using individual interviews, focus groups, and surveys have explored the recollections and perceptions of hospice staff, 12 family members, 13 and EMS providers [14][15][16][17][18][19][20][21][22][23] of the role of EMS and hospitalization in palliative care. (It should be noted that terms like "palliative care" are sometimes used loosely in the literature, and it may not be limited to patients formally enrolled in a hospice program.)…”
Section: Introductionmentioning
confidence: 99%